2017
DOI: 10.1371/journal.pone.0169114
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Light Filtering Spectacle Lenses: Optical and Clinical Performances

Abstract: PurposesTo evaluate the optical performance of blue-light filtering spectacle lenses and investigate whether a reduction in blue light transmission affects visual performance and sleep quality.MethodsExperiment 1: The relative changes in phototoxicity, scotopic sensitivity, and melatonin suppression of five blue-light filtering plano spectacle lenses were calculated based on their spectral transmittances measured by a spectrophotometer. Experiment 2: A pseudo-randomized controlled study was conducted to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 46 publications
1
79
0
17
Order By: Relevance
“…We included three studies in this review . Two of the studies were conducted in the USA and one in Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…We included three studies in this review . Two of the studies were conducted in the USA and one in Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…16 The optical and clinical performance of blue light-blocking spectacle lenses has been relatively understudied compared with blue light-filtering intraocular lenses. 17,18 Leung et al 9 conducted a pseudo-randomised study to investigate if blue light attenuation affected visual performance and sleep quality. The study outcomes, after 1 month of blue light-blocking lens wear, showed no significant difference in contrast testing (with and without glare), colour discrimination, or sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…[6] For this reason, many different filters that reduce that part of the visible spectrum have been developed in order to reduce the effect of blue light on the retina. [7] The nanomaterial based on fullerene C60 and PMMA has been used for nanophotonic contact lenses [8] and spectacles. [9] It has been shown to transform diffuse light into harmonised and hyper-polarised light and these light photons have the same symmetry order (electrical and magnetic planes of photons in space and time) as biomolecules, which interact with light.…”
Section: Introductionmentioning
confidence: 99%